A hybrid method of estimating pulsating flow parameters in the space-time domain. (15th May 2017) - Pałczyński, Tomasz
Abstract: This paper presents a method for estimating pulsating flow parameters in partially open pipes, such as pipelines, internal combustion engine inlets, exhaust pipes and piston compressors. The procedure is based on the method of characteristics, and employs a combination of measurements and simulations. An experimental test rig is described, which enables pressure, temperature and mass flow rate to be measured within a defined cross section. The second part of the paper discusses the main assumptions of a simulation algorithm elaborated in the Matlab/Simulink environment. The simulation results are shown as 3D plots in the space-time domain, and compared with proposed models of phenomena relating to wave propagation, boundary conditions, acoustics and fluid mechanics. The simulation results are finally compared with acoustic phenomena, with an emphasis on the identification of resonant frequencies. Highlights: Principles of method of characteristics are presented. Boundary conditions for pressure and velocity at opened, closed and partially opened ends. Experimental background and measurement data. Simulation results and conclusions.